The Role of 7P Marketing Mix toward Consumer Satisfaction and Loyalty of XYZ Beauty Clinic - Ade Agusti Alwinie; Popong Nurhayati; Bagus Sartono (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2024)
The XYZ Beauty Clinic has many branches throughout Indonesia, including the Metropolitan Mall (MM) Bekasi branch, which has been established since 2011. Over time, the XYZ MM Clinic has faced various challenges, such as a decrease in the frequency of customer visits. This study aims to analyze consumer perceptions, factors that affect consumer satisfaction and loyalty, and the level of satisfaction and loyalty of XYZ Beauty Clinic consumers. The study used a cross-sectional design. The sampling technique used purposive sampling involving 152 respondents who were at least 17 years old and had visited at least twice in the last year. Data were processed quantitatively using SEM-PLS, Customer Satisfaction Index (CSI), and Customer Loyalty Index (CLI) to test the hypotheses and measure the level of consumer satisfaction and loyalty. The results indicated that consumer perception with low satisfaction and low loyalty are consumers who work as entrepreneurs, consumers who earn less than 5 million a month, as well as consumers who live in Tangerang and Bogor. The marketing mix that affects consumer satisfaction includes product, promotion, process, people, and physical evidence. Customer satisfaction affects customer loyalty. The level of customer satisfaction shows satisfactory results and the level of customer loyalty shows loyal results. Based on the research results, clinics are advised to prioritize consumer groups with low perceptions of satisfaction